Ocean acidification does not impact shell growth or repair of the Antarctic brachiopod Liothyrella uva (Broderip, 1833) - Cross, Emma L.; Peck, Lloyd S.; Harper, Elizabeth M. (Journal of Experimental Marine Biology and Ecology, 2015)
Marine calcifiers are amongst the most vulnerable organisms to ocean acidification due to reduction in the availability of carbonate ions for skeletal/shell deposition. However, there are limited long-term studies on the possible impacts of increased pCO2 on these taxa. A 7month CO2 perturbation experiment was performed on one of the most calcium carbonate dependent species, the Antarctic brachiopod Liothyrella uva, which inhabits the Southern Ocean where carbonate ion saturation levels are amongst the lowest on Earth. The effects of the predicted environmental conditions in 2050 and 2100 on the growth rate and ability to repair shell in L. uva were tested with four treatments; a low temperature control (0°C, pH7.98), a pH control (2°C, pH8.05), mid-century scenario (2°C, pH7.75) and end-century scenario (2°C, pH7.54). Environmental change impacts on shell repair are rarely studied, but here repair was not affected by either acidified conditions or temperature. Growth rate was also not impacted by low pH. Elevated temperature did, however, increase growth rates. The ability of L. uva to continue, and even increase shell production in warmer and acidified seawater suggests that this species can acclimate to these combined stressors and generate suitable conditions for shell growth at the site of calcification.
Keywords: CO; Calcification; Carbonate saturation; Climate change; dept.egm; pH

Long-term effects of altered pH and temperature on the feeding energetics of the Antarctic sea urchin, Sterechinus neumayeri - Morley, Simon A., Coleen C., Suckling, Melody S., Clark, Emma L., Cross; Peck, Lloyd S. (Biodiversity, 2016)
This study investigated the effects of long-term incubation to near-future combined warming (+2 °C) and ocean acidification (−0.3 and −0.5 pH units) stressors, relative to current conditions (−0.3 °C and pH 8.0), on the energetics of food processing in the Antarctic sea urchin, Sterechinus neumayeri. After an extended incubation of 40 months, energy absorbed, energy lost through respiration and lost as waste were monitored through two feeding cycles. Growth parameters (mass of somatic and gonad tissues and the CHN content of gonad) were also measured. There were no significant effects of combined ocean acidification (OA) and temperature stressors on the growth of somatic or reproductive tissue. Despite more food being consumed in the low temperature control, once food processing and maintenance costs were subtracted, there were no significant effects of treatment on the scope for growth. The biggest significant differences were between amounts of food consumed during the two feeding cycles. More food was consumed by the low temperature (0 °C) control animals, indicating a potential effect of the changed conditions on digestive efficiency. Also, in November, more food was consumed, with a higher absorption efficiency, which resulted in a higher scope for growth in November than September and may reflect increased energetic needs associated with a switch to summer physiology. The effect of endogenous seasonal cycles and environmental variability on organism capacity is discussed.
_eprint: https://doi.org/10.1080/14888386.2016.1174956
Keywords: Carbonate saturation; climate change; dept.egm; echinoderm; energetics; ocean acidification; peer-reviewed; physiology; resilience

No ocean acidification effects on shell growth and repair in the New Zealand brachiopod Calloria inconspicua (Sowerby, 1846) - Cross, Emma L.; Peck, Lloyd S.; Lamare, Miles D.; Harper, Elizabeth M. (ICES Journal of Marine Science, 2016)
Surface seawaters are becoming more acidic due to the absorption of rising anthropogenic CO2. Marine calcifiers are considered to be the most vulnerable organisms to ocean acidification due to the reduction in the availability of carbonate ions for shell or skeletal production. Rhychonelliform brachiopods are potentially one of the most calcium carbonate-dependent groups of marine organisms because of their large skeletal content. Little is known, however, about the effects of lowered pH on these taxa. A CO2 perturbation experiment was performed on the New Zealand terebratulide brachiopod Calloria inconspicua to investigate the effects of pH conditions predicted for 2050 and 2100 on the growth rate and ability to repair shell. Three treatments were used: an ambient pH control (pH 8.16), a mid-century scenario (pH 7.79), and an end-century scenario (pH 7.62). The ability to repair shell was not affected by acidified conditions with >80% of all damaged individuals at the start of the experiment completing shell repair after 12 weeks. Growth rates in undamaged individuals >3 mm in length were also not affected by lowered pH conditions, whereas undamaged individuals <3 mm grew faster at pH 7.62 than the control. The capability of C. inconspicua to continue shell production and repair under acidified conditions suggests that this species has a robust control over the calcification process, where suitable conditions at the site of calcification can be generated across a range of pH conditions.
Keywords: dept.egm; peer-reviewed

Warning: Extinction Ahead! Theorizing the Spatial Disruption and Place Contestation of Climate Justice Activism - Axon, Stephen (Environment, Space, Place, 2019)
Since 31 October 2018, Extinction Rebellion has advocated in numerous examples of civil disobedience across the UK in an attempt to call for further action to address climate change. Following this example, similar activism has also been seen across Europe and North America. Such activism falls within the context of climate justice (the framing of climate change as an ethical and political issue); given the disproportionate impacts that climate change has on the most vulnerable people in society, e.g., low-income communities, women, and future generations. What is noticeable about Extinction Rebellion is its ability to place climate change on the social agenda, a task that has proven difficult in the age of denialism, skepticism, false-balance media reporting, and far-right politics. With reference to recent examples of civil disobedience and protests in 2019, this paper evaluates how climate justice movements, specifically Extinction Rebellion, change meanings of urban landscapes into becoming more contested places and disrupt the consciousness of everyday routines toward sustainability. This disruption and contested nature is brought about through changing the sociocultural dynamics of urban landscapes during, and after, such protests. The meanings of urban landscapes thus change from being viewed as purely sites of materialist consumption to sites of initial resistance against business-as-usual approaches to climate change leading to changes in policy. Through substantial public engagement with the narrative of climate justice, civil disobedience protests, and urban art, it is clear that urban areas “held” for a number of successive days have started to be perceived differently. This article concludes with implications for subsequent spatial disruption and civil disobedience advocating for stronger climate policy.
Keywords: dept.egm; peer-reviewed

History of Geography as a Science in the Republic of Paraguay. - Yacher, Leon I. (2010)
Keywords: dept.egm; faculty_collection; sabbatical_report

Towards Coastal Resilience and Sustainability - Heidkamp, C. Patrick; Morrissey, John; Graves, Scott M. (Routledge, 2019)
"Coastal zones represent a frontline in the battle for sustainability, as coastal communities face unprecedented economic challenges. Coastal ecosystems are subject to overuse, loss of resilience and increased vulnerability. This book aims to interrogate the multi-scalar complexities in creating a more sustainable coastal zone. Sustainability transitions are geographical processes, which happen in situated, particular places. However, much contemporary discussion of transition is either aspatial or based on implicit assumptions about spatial homogeneity. This book addresses these limitations through an examination of socio-technological transitions with an explicitly spatial focus in the context of the coastal zone. The book begins by focusing on theoretical understandings of transition processes specific to the coastal zone and includes detailed empirical case studies. The second half of the book appraises governance initiatives in coastal zones and their efficacy. The authors conclude with an implicit theme of social and environmental justice in coastal sustainability transitions. Research will be of interest to practitioners, academics and decision-makers active in the sphere of coastal sustainability. The multi-disciplinary nature encourages accessibility for individuals working in the fields of Economic Geography, Regional Development, Public Policy and Planning, Environmental Studies, Social Geography and Sociology" – Provided by publisher's website.
Keywords: Coastal zone management; Economic aspects; Economic aspects; Sustainable development; dept.egm; faculty_collection

Sabbatical leave report: Spring 2014 - Heidkamp, C. Patrick (2014)
The proposed research project focused on analyzing food system resilience in a small town in eastern Iceland from the perspective of environmental economic geography. In addition to the stated project Heidkamp initiated "a new research project focused on the uniqueness of Nordic Environments, Nordic Spaces and Nordic Places." The sabbatical study yielded panelist and lecturer invitations and conference papers and presentations.
Keywords: dept.egm; faculty_collection; sabbatical_report

Raptors of the Northeast - Bosakowski, Thomas; Smith, Dwight G. (Coachwhip Publications, 2010)
Keywords: Birds of prey; Identification; Identification; Birds; Northeastern States; dept.egm; faculty_collection

Sabbatical leave report: sabbatical Spring 2010 - Yacher, Leon I. (2010)
The purpose of the project was to travel to Paraguay to explore the history of geography as a science in that country, including identifying the foremost geographers who helped introduce and establish geography as a science in that country. No such study on the history of geography in Paraguay had been previously undertaken anywhere. Further research will be needed, but the collected material is ample for at least two article-length publications.
Keywords: dept.egm; faculty_collection

Blue Economy - Germond-Duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2016)
Geography has engaged in insightful discussions on how to understand, analyze, criticize, and implement the blue economy. United Nations agencies, Small Island Developing States, and increased academic interest in oceans have played important roles in the global adoption of the blue economy idea, that is, the sustainable exploitation of marine and coastal resources. Geographical research on the blue economy has addressed key themes such as economic and political discourse, relational thinking and assemblage, sustainability and just transitions, and blue economy risks.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118786352.wbieg2166
Keywords: coastal and marine geography; dept.egm; economic development; environmental management; sustainable development

Multifaceted NOS instruction: Contextualizing nature of science with documentary films - Bloom, M.; Binns, I.C.; Koehler, C. (International Journal of Environmental and Science Education, 2015)
This research focuses on inservice science teachers’ conceptions of nature of science (NOS) before and after a two-week intensive summer professional development (PD). The PD combined traditional explicit NOS instruction, numerous interactive interventions that highlighted NOS aspects, along with documentary films that portrayed NOS in context of authentic scientific discovery. Reflective dialogue was used throughout the professional development to encourage constructivist learning. The PD addressed seven commonly held NOS tenets that are deemed significant to K-12 science teachers. Finally, qualitative methodologies were used to analyze the Views of Nature of Science Questionnaire (VNOS-D) and the associated interview data to explore subtleties within each NOS tenet and to gain a richer understanding of how the teachers’ NOS understanding differed before and after the PD. © 2015 by iSER, International Society of Educational Research.
Keywords: Contextualized instruction; Nature of science; Professional development; dept.egm; ⚠️ Invalid DOI

Observations of the Influence of Regional Beach Dynamics on the Impacts of Storm Waves on the Connecticut Coast During Hurricanes Irene and Sandy - Tait, James F.; Ferrand, Ezgi Akpinar (Learning from the Impacts of Superstorm Sandy, 2015)
The Connecticut shoreline is one of the most intensively developed in the country. In many locations, development has relied on the buffering capacity of broad beaches for protection against storms. Much of this development is at risk due to an insufficient understanding of regional beach dynamics. The coast is commonly regarded as “protected” by the presence of Long Island. Nonetheless, Irene and Sandy imposed significant property losses on coastal cities. The most severe damages were due to wave impact in areas with narrow beaches. Small differences (as little as 21 m) in beach width proved to be significant during these storms. Sheltering by Long Island does not prevent coastal erosion during local storms. In the long run, it does prevent the rebuilding of the beach during fair weather by limiting the energy available for shoreward transport. This dynamic makes the beaches naturally erosive and their buffering capacity transient at best.
Keywords: Beach erosion; Beaches; Buffering capacities; Coastal cities; Coastal erosion; Connecticut beach dynamics; Dynamics; Energy asymmetry; Erosion; Fair weather; Hurricane Irene; Hurricane Sandy; Hurricanes; Property loss; Storm wave impacts; Storm waves; Storms; Water waves; beach erosion; dept.egm; energy asymmetry; faculty_collection; storm wave impacts

The emergence of stem - Koehler, C.; Binns, I.C.; Bloom, M.A. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Journal Abbreviation: STEM Road Map: A Framew. for Integr. STEM Educ.
Keywords: dept.egm

The stem road map for grades k-2 - Koehler, C.; Bloom, M.A.; Milner, A.R. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Journal Abbreviation: STEM Road Map: A Framew. for Integr. STEM Educ.
Keywords: dept.egm

The Kyrgyz Republic,1 central Asia, and daily life engagement - Yacher, L. (Arab World Geographer, 2016)
Keywords: Central Asia; Kyrgyzstan; dept.egm; geographical thought; life satisfaction; perception; ⛔ No DOI found

Urban food production limits and the viability of community gardens: The case of hartford, connecticut - Heidkamp, C.P.; Russell, S.E.; Sloan, M. (Local Food Systems in Old Industrial Regions: Concepts, Spatial Context, and Local Practices, 2012)
Hartford, the state capital of Connecticut, is a typical example of a former manufacturing oriented1 industrial city and, like much of the urban northeastern United States, has gone through a period of economic deindustrialization and consequent urban decay. Since the departure of the manufacturing base, Hartford has refocused its economic development on the service economy, and first and foremost, the insurance industry. The city even proclaims itself the “insurance capital of the world.” Yet, even though the insurance industry as well as other service oriented development strategies (a new convention center, science museum, and retail developments) have been quite successful in fostering economic activity and attracting employees (mostly residents of the surrounding suburbs commuting into white collar jobs), the spatial manifestations of deindustrialization are still visible and persistent in the physical as well as the social fabric of the city. © 2012 Neil Reid, Jay D. Gatrell and Paula S. Ross All rights reserved.
Journal Abbreviation: Local Food Systems in Old Industrial Regions: Concepts, Spatial Context, and Local Practices
Keywords: dept.egm

Introduction: Sustainability in the coastal zone - Heidkamp, C.P.; Morrissey, J. (Towards Coast. Resil. and Sustainability, 2018)
Coastal areas provide many co-benefits associated with their natural infrastructure, facilitating activities such as fishing, industry, tourism and transportation, for instance (Barragán & de Andrés, 2015; Sutton-Grier, Wowk & Bamford, 2015). Despite occupying a relatively small percentage of the Earth's land surface, the value of the ecosystems’ services of coastal areas is more than one-third of the total for the globe (Barbier et al., 2011; Barragán & de Andrés, 2015). However, while the goods and services provided by coastal ecosystems are essential for economic and social well-being (Mavrommati, Bithas & Panayiotidis, 2013), coastal ecosystems are increasingly at risk. As a direct result of intensive resource use and of concentrations of population, coastal ecosystems increasingly demonstrate direct and adverse impacts of human activities (Swaney et al., 2012). Increasing population growth, movement of populations towards the coast and the increase in coastal development have led to an increase in pressure on, and degradation of, coastal ecosystems (Duxbury & Dickinson, 2007). For large coastal cities, interactions between human activities and coastal systems are intensified due to population density effects and associated economic activities (Mavrommati et al., 2013). In many parts of the world, coastal natural habitats are declining and overexploited coastal resources are dwindling, with associated impacts on ecosystems and on the livelihoods dependent on these (Mee, 2012). © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Journal Abbreviation: Towards Coast. Resil. and Sustainability
Keywords: Coastal development; Coastal ecosystems; Coastal resources; Coastal zones; Economic activities; Economics; Ecosystems; Increase in pressure; Population densities; Population growth; Population statistics; Social well-being; dept.egm

Testate amoebae of peru: Filling the gap in the Neotropics - Bobrov, A.; Mazei, Y.; Buyvolova, A.; Yacher, L. (Revista de Biologia Tropical, 2019)
Testate amoebae diversity from 28 surface (0-3 cm depth) soil samples found near Cuzco (6 samples), in Machu Piсchu (17 samples), in Aguas Calientes (5 samples), and one bottom sediment sample from the Lake Titicaca near Puno were collected during March of 2016 were analyzed. The 144 testate amoebae species and infra-specific taxa belonging to 27 genera were identified. Nineteen amoebae have not been identified to species level and likely represent new taxa. Species richness varied from one to 54 taxa per sample. The highest diversity was found in rainforests followed by those in meadows and agave habitats. The only bottom sample from Lake Titicaca has yielded two hydrobiont species from the genus Difflugia. In the course of the study, several rare species with limited geographical distribution were observed, namely Centropyxis castaneus, C. compressa, C. deflandriana, C. latideflandriana, C. cf. ohridensis, C. cf. ovoides, C. cf. pannosus, C. stenodeflandriana, Cyclopyxis plana, C. profundistoma, Apodera vas, Argynnia retorta, A. spicata, Certesella certesi, Trachelcorythion pulchellum. Our study fills a geographical gap in the distribution of some flagship species with restricted geographic distribution, e.g. Apodera vas and Certesella certesi in Peru. The results illustrate the continuity of expansion species along the Pacific coast. © 2019 by Revista de Biologia Tropical. All rights reserved.
Keywords: Biodiversity; Biogeography; Mountain rainforest; Peru; Protista; dept.egm; peer-reviewed; ⛔ No DOI found

Book Review: Responses to elizabeth j. mueller review of the city reader, 5th ed., and/or the american urban reader: history and theory - Wuerzer, Thomas; Wang, Jing; Klotz, Marilyn; Holt, William G. (Journal of Urban Affairs, 2012)
0 citations (Crossref) [2023-10-31] tex.orcid-numbers: Wuerzer, Thomas/0000-0002-8290-3785 tex.researcherid-numbers: Wuerzer, Thomas/F-1017-2014 tex.unique-id: ISI:000299630500014
Keywords: book.review; dept.egm

Maynard weston dow (1929–2011) and “Geographers on film” - Martin, Geoffrey J (Annals of The Association of American Geographers, 2013)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-899-990-263-922 tex.type: [object Object]
Keywords: art; dept.egm

Education reform: the past, the present, and the future? - Koehler, Catherine M (School Science and Mathematics, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/077-125-641-648-724 tex.type: [object Object]
Keywords: dept.egm

Lights, camera, action! Developing a methodology to document mainstream films’ portrayal of nature of science and scientific inquiry - Koehler, Catherine M; Bloom, Mark; Binns, Ian C (The Electronic Journal of Science Education, 2013)
Citation Key Alias: lens.org/117-629-120-125-07X tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Lessons learned from professional development from a faculty Member/Student lens - Koehler, Catherine M (School Science and Mathematics, 2015)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-953-204-175-051 tex.type: [object Object]
Keywords: dept.egm

American Geography and Geographers: Toward Geographical Science - Martin, Geoffrey J. (Oxford University Press, 2014)
The rise of American geography as a distinctive science in the United States straddles the 19th and 20th centuries, extending from the post-Civil war period to 1970. American Geography and Geographers: Toward Geographic Science is the first book to thoroughly and richly explicate this history. Its author, Geoffrey J. Martin, the foremost historian on the subject and official archivist of the Association of American Geographers, amassed a wealth of primary sources from archives worldwide, which enable him to chart the evolution of American geography with unprecedented detail and context. From the initial influence of the German school to the emergence of Geography as a unique discipline in American universities and thereafter, Martin clarifies the what, how and when of each advancement. Expansive discussion of the arguments made, controversies ignited and research voyages move hand in hand with the principals who originated and animated them: Davis, Jefferson, Huntington, Bowman, Johnson,, Sauer, Hartshorne, and many more. From their grasp of local, regional, global and cultural phenomena, geographers also played pivotal roles in world historical events, including the two world wars and their treaties, as the US became the dominant global power. American Geography and Geographers: Toward Geographical Science is a conclusive study of the birth and maturation of the science. It will be of interest to geographers, teachers and students of geography, and all those compelled by the story of American Geography and those who founded and developed it.
Keywords: Geography; History; History; Geographers; History; United States; Study and teaching; Study and teaching (Higher); United States; dept.egm; faculty_collection

Residential perspectives: the value of Floodplain‐ buyout open space - Zavar, Elyse (Geographical Review, 2015)
This mixed-methods case study identifies how floodplain property acquisitiona buyoutimpacts an urban environment at the neighborhood scale while considering the role of individual residents in formal and informal land-use decision making. In floodplain buyouts, the reopening of urban space is enabled by federal structural drivers, primarily Federal Emergency Management Agency (FEMA), but it is repurposed as a cultural landscape constructed and produced by individuals. This research explores how residents perceive and ascribe values to the buyout landscape in Lexington, Kentucky. Enabled by federal funds, but left largely to their own devices, residents in Lexington adopted uses, ascribed values, and produced their own land-use norms in each buyout neighborhood.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-849-610-654-018 tex.type: [object Object]
Keywords: dept.egm; floodplain; land management; land value; peer-reviewed; property acquisition

The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-794-376-727-198 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space

Especies de jaltomata schltdl. (solanaceae) con néctar rojo, tres nuevas combinaciones nomenclaturales y un nuevo taxón del noreste de perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2016)
Citation Key Alias: lens.org/148-203-876-064-621 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

The Modifiable Conceptual Unit Problem demonstrated using pollen and seed dispersal - Miller, Matthew D (Global Ecology and Conservation, 2016)
The Modifiable Areal Unit Problem (MAUP) is a famous issue in spatial analysis that states the output of a spatial analysis is influenced by the spatial extent of the units used in the analysis. This study demonstrates that the MAUP is accompanied with another intractable spatial issue in spatial modeling; the Modifiable Conceptual Unit Problem (MCUP). The MCUP states that the conceptualization of spatial processes impacts the output of spatial analysis and occurs when a model with one spatial dimension is applied to a spatial model with more than one spatial dimension. This study demonstrates the MCUP by developing three conceptual models of dispersal and showing how they produce different results even when given the same initial dispersal curves and areal units. Three conceptual models of dispersal (sum of curve points model, area of distance range model, and the volume of distance range model) are described and applied to a grid landscape with a single point of dispersal and a grid landscape with multiple points of dispersal. A Geographic Information System (GIS) is used to evaluate how the models differ in their distribution of pollen or seeds across the landscapes. The three models of dispersal are each valid conceptualizations of the dispersal process, but when given the same dispersal curve parameters, they produce different distributions of dispersed items across grid landscapes. The sum of curve points model is the least complicated model because it only uses a few points from the defined dispersal curve. The area of distance range model uses the entire dispersal curve, but is based on a single dimension of space and thus conceptually abstracted from the grid landscape. The volume of distance range model uses the two spatial dimensions present in the grid landscape and thus is the most conceptually sound model of the three. The underlying conceptualization of the dispersal process can impact the results of dispersal models. Applying dispersal curves with one spatial dimension to grids with two spatial dimensions makes inherent assumptions about the conceptualization of dispersal. This study highlights the necessity of researchers to declare their conceptual models of dispersal when applying modeled dispersal curves to grid landscapes. © 2016 The Author.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-510-462-186-063 tex.type: [object Object]
Keywords: Conceptual; Dispersal; Grid; MAUP; Pollen; Spatial; dept.egm

Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-423-912-140-83X tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm

Jaltomata anteropilosa (Solanaceae) una nueva especie del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Keywords: dept.egm; ⛔ No DOI found

Jaltomata athahuallpae (solanaceae), una nueva especie del norte del perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: pop00375 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Jaltomata glomeruliflora (Solanaceae) una nueva especie del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: pop00377 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Rainwater Harvesting as an Effective Climate Change Adaptation Strategy in Rural and Urban Settings - Ferrand, Ezgi Akpinar (Managing Water Resources under Climate Uncertainty: Examples from Asia, Europe, Latin America, and Australia, 2015)
Human societies are known for their resilience and ability to adapt to short- and long-term environmental change. Despite their pragmatism and adaptability, humans could be forced to move and/or seek better conditions for survival, especially when climate change and water availability are at issue. This chapter provides case studies on easy-to-adopt rainwater harvesting applications as effective climate change adaptation strategies in rural and urban settings to increase human resiliency.
Citation Key Alias: lens.org/158-085-691-782-246
Keywords: Climate Change Adaptation; Climate change adaptation; Rainwater Harvesting; Rainwater harvesting; Urban and Rural Settings; Urban and rural settings; dept.egm

Jaltomata angasmarcae y jaltomata pauciseminata (solanaceae), dos nuevas especies del norte del perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2015)
Citation Key Alias: lens.org/107-286-838-809-425 tex.type: [object Object]
Keywords: dept.egm; ⚠️ Invalid DOI

Two new Peruvian species of Jaltomata (Solanaceae, Solaneae) with red floral nectar - Mione, Thomas; González, Segundo Leiva; Yacher, Leon (Brittonia, 2014)
Two new Jaltomata species (Solanaceae) of Peru that produce red floral nectar are described. Jaltomata neei of Department Cajamarca has 1–4 flowers per inflorescence, the campanulate corolla is green and then changes to blue, corolla lobes (5) and lobules (5) are equally prominent, a corona is lacking, five radial staminal-corolla thickenings create nectar troughs between, and the stigma is capitate. Jaltomata quipuscoae of Department Arequipa has solitary flowers, a purple, broadly crateriform, 5-lobed corolla, a corona on which nectar pools, a punctiform stigma, lacks corolla thickenings, and the mature fruit is whitish. Photographs, illustrations and tables are included that allow comparison with closely related species. © 2014, The New York Botanical Garden.
10 citations (Crossref) [2023-10-31] Citation Key Alias: pop00141 tex.type: [object Object]
Keywords: Arequipa; Cajamarca; Jaltomata neei; Jaltomata quipuscoae; Peru; corolla color change; corona; dept.egm; lomas; protogyny; red nectar

Potential of rainwater harvesting in a thirsty world: A survey of ancient and traditional rainwater harvesting applications - Ferrand, Ezgi Akpinar; Cecunjanin, Fatima (Geography Compass, 2014)
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-046-559-732-638 tex.type: [object Object]
Keywords: dept.egm; peer-reviewed

Metals, Organic Compounds, and Nutrients in Long Island Sound: Sources, Magnitudes, Trends, and Impacts - Varekamp, Johan C.; McElroy, Anne E.; Mullaney, John R.; Breslin, Vincent T. (Long Island Sound: Prospects for the Urban Sea, 2014)
Long Island Sound (LIS) is a relatively shallow estuary with a mean depth of 20 m (maximum depth 49 m) and a unique hydrology and history of pollutant loading. These factors have contributed to a wide variety of contamination problems in its muddy sediments, aquatic life, and water column. The LIS sediments are contaminated with toxic compounds and elements related to past and present wastewater discharges and runoff. These include nonpoint and stormwater runoff and groundwater discharges, whose character has changed over the years along with the evolution of its watershed and industrial history. Major impacts have resulted from the copious amounts of nutrients discharged into LIS through atmospheric deposition, domestic and industrial waste water flows, fertilizer releases, and urban runoff. All these sources and their effects are in essence the result of human presence and activities in the watershed, and the severity of pollutant loading and their impacts generally scales with total population in the watersheds surrounding LIS. Environmental legislation passed since the mid-to-late 1900s (e.g., Clean Air Act, Clean Water Act) has had a beneficial effect, however, and contaminant loadings for many toxic organic and inorganic chemicals and nutrients have diminished over the last few decades (O’Shea and Brosnan 2000; Trench et al. 2012; O’Connor and Lauenstein 2006; USEPA 2007). Major strides have been made in reducing the inflow of nutrients into LIS, but cultural eutrophication is still an ongoing problem and nutrient control efforts will need to continue. Nonetheless, LIS is still a heavily human impacted estuary (an “Urban Estuary,” as described for San Francisco Bay by Conomos 1979), and severe changes in water quality and sediment toxicity as well as ecosystem shifts have occurred since the European colonization in the early 1600s (Koppelman et al., 1976). The Sound has seen the most severe environmental changes over the last 400 years during its 10,000 year history (Lewis, this volume), suggesting that human impacts have overwhelmed the natural forces at play.
Citation Key Alias: lens.org/113-875-687-538-455
Keywords: Boston Harbor; Coastal Embayment; Marine Organic Matter; Striped Bass; White Perch; dept.egm

Forest cover change in the northeastern U.S.: A spatial assessment in the context of an environmental kuznets curve - Bentley, George C; Cromley, Robert G; Hanink, Dean M; Heidkamp, C Patrick (International Journal of Applied Geospatial Research, 2013)
An analysis of the association of forest cover, treated as an environmental good, and income at the county scale in the Northeastern United States was conducted for 2006. Global analysis using a spatial error regression model indicates an environmental Kuznets curve (EKC) type of relationship, with total forest cover, percent forest cover, and forest cover per capita is better associated with per capita income and is better specified as a polynomial rather than in linear terms. Local analysis, using geographically weighted regression, indicates that sub-regional effects are pronounced, and that conformity to an EKC varies spatially and by forest cover measure. The findings should be interpreted strictly within their context of a cross-sectional analysis and within certain statistical limitations, primarily engendered by multicollinearity of the explanatory variables in the regression models. Copyright © 2013, IGI Global.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-145-892-110-132 tex.type: [object Object]
Keywords: Environmental Kuznets Curve; Forest Cover; Geographically Weighted Regression; Northeastern United States; Spatial Error Regression Model; dept.egm

Tax lien sales as local neoliberal governance strategy: The case of Waterbury, Connecticut - Botein, Hilary; Heidkamp, C Patrick (Local Economy, 2013)
This article examines bulk sales of municipal property tax liens in the formerly industrial city of Waterbury, Connecticut, USA, in the 1990s, in order to explore the limits and contradictions of neoliberal local governance strategies. In the USA, cities and states create property tax liens by reducing delinquent real estate taxes to a judgment that creates a legal claim against the property at issue. We argue that Waterbury's efforts to resolve its fiscal stress by enhancing short-term revenues ultimately further constrained its revenue base, the tax lien sales reflected a spatial selectivity that created barriers to revitalization when neither the city nor tax lien purchasers had incentives to foreclose on distressed properties in struggling neighborhoods, and the tax lien sales' failure to resolve the city's budget crisis set in motion new efforts at tax base enhancement through real estate-led development in the central business district that also were unsuccessful. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-820-978-161-106 tex.type: [object Object]
Keywords: dept.egm; housing; local government; neighbourhood decline; neoliberalism; real estate taxes; tax liens; urban governance

Use of aguadas as water management sources in two southern maya lowland sites - Ferrand, Ezgi Akpinar; Dunning, Nicholas P; Lentz, David L; Jones, John G (Ancient Mesoamerica, 2012)
Aguadas, either natural or human-made ponds, were significant sources of water for the ancient Maya. Aguadas are common features in the Maya Lowlands and make valuable locations for collecting archaeological and paleoenvironmental data. This article discusses research conducted at four aguadas around two adjacent Maya sites, San Bartolo and Xultun in Peten, Guatemala. Both San Bartolo and Xultun were established during the Preclassic period. However, the fates of the two sites differed, as Xultun continued to prosper while the city of San Bartolo was abandoned near the close of the Late Preclassic period. We argue that aguadas provide important clues for understanding the fate of these two ancient communities and many others in the Maya Lowlands. Copyright © 2012 Cambridge University Press.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-122-134-377-577 tex.type: [object Object]
Keywords: Guatemala [Central America]; Maya Lowlands; Peten; San Bartolo; archaeological evidence; dept.egm; paleoenvironment; planning history; urban planning; water management; water resource; water use

Where to begin? Getting started teaching GIS&T - West, Eric (Teaching Geographic Information Science and Technology in Higher Education, 2012)
tex.type: Proceedings paper
Keywords: Coordinating lectures; Exercise style; Faculty teaching GIS&T; Global positioning system; Global positioning systems (GPS); Goals; for courses; Inquiry instruction; Learning objective; in BoK; Learning objectives; Teaching; Teaching GIS&T; dept.egm

Book Review: The nature of new york: an environmental history of the empire state - Harrison, Blake (Environmental History, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-257-073-142-557 tex.type: [object Object]
Keywords: book.review; dept.egm

Natural protest: essays on the history of american environmentalism - Harrison, Blake (Environmental History, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-408-577-232-671 tex.type: [object Object]
Keywords: book.review; dept.egm

‘Food desertification’: The loss of a major supermarket in New Haven, Connecticut - Russell, Scott E; Heidkamp, C Patrick (Applied Geography, 2011)
In March of 2010, the only full-service supermarket centrally located in New Haven, Connecticut closed, stranding many of the city's residents in a food desert. A food desert is an urban or rural area with significantly limited access to retail sources of healthy and affordable food, due to a combination of socioeconomic disadvantages and physical distance. This article considers the pivotal and causative role of the business model of supermarkets in the creation of new or exacerbation of current urban food deserts, as well as in the impact the loss of one market has on the resilience of the community's food system. Using the events of New Haven as a case study, the form and severity of the food desert in New Haven is analyzed by mapping 1/4 mile, 1/2 mile, and 1 mile road network service areas of the major supermarkets and grocery stores of the area. These are compared against Census block group data of the New Haven population's median household income, poverty level, and access to a personal vehicle. The results show certain parts of the city with low income, high poverty, and low vehicle access to exist in hardship outside the service areas of nearby stores. GIS methodology aids in illustrating the conclusion that the loss of just one supermarket has had significantly detrimental effects on the geographical food access of the city's residents. The ongoing lack of a full-service supermarket in the city not only raises concerns about the value of a new supermarket coming in, but also creates possibilities for seeking alternative food system solutions. (C) 2011 Elsevier Ltd. All rights reserved.
80 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000292537700002, lens.org/010-795-278-274-239 tex.type: [object Object]
Keywords: Connecticut; Food deserts; Food security; GIS; Geographic information systems (GIS); New Haven; Supermarkets; United States; Urban food systems; consumption behavior; dept.egm; food consumption; mapping method; retailing; spatial analysis

Astana, Kazakhstan: Megadream, Megacity, Megadestiny? - Yacher, Leon (Engineering Earth: The Impacts of Megaengineering Projects, 2011)
Astana, Kazakhstan’s new capital city is being built to fit the future vision of the country’s leaders. Unique architectural styles, combined with creative morphological patterns give the city a distinctive look. It is being constructed to impress. It also represents a break from the past. As such, Astana embodies the meaning of a ‘Forward city.’ Forward cities are created for a variety of reasons; political, geopolitical, religious, economic or a combination of these. By relocating a capital city elsewhere, a country seeks to construct a fresh urban site that reflects a change from the traditional center of governmental activities to a new location that reveals a new direction for the country and its people. This chapter provides a brief background of the political context and conditions existing in the region, followed by an overview of the city’s geographic base, and scrutinize the unique methods of finance used to construct Astana. Also, the planning and design of the city will be examined, paying special attention to the ways in which architecture has been utilized to construct a futuristic vision of a public project for domestic and international consumption.
Citation Key Alias: lens.org/000-386-017-547-147
Keywords: Capital City; Kyrgyz Republic; Presidential Decree; Soviet Republic; Special Economic Zone; dept.egm

Mobility, farmworkers, and Connecticut's tobacco valley, 1900–1950 - Harrison, Blake (Journal of Historical Geography, 2010)
By the early decades of the twentieth century, southern New England's Connecticut Valley had become a center of shade tobacco production and a destination for seasonal farmworkers drawn from sources inside and outside of New England. This paper explores the history of three groups of seasonal workers-children from area cities and towns; white southern high school students: and young African American men from southern high schools and black colleges-with an eye to assessing the impact of their presence on the form and meaning of the Connecticut Valley. My first goal is to add depth to the historiography of twentieth-century New England farming by drawing attention to the largely overlooked story of non-rural and extra-regional seasonal farmworkers. My second goal is to frame the case of Connecticut tobacco labor according to the study of mobility and its relationship to landscape. The mobility of workers into and within the region, I suggest, made possible the success of the shade tobacco economy while at the same time posing challenges to popularized cultural conventions about regional identity. For this reason, I argue, the history of Connecticut's shade tobacco landscape was informed by the efforts of shade tobacco growers to direct and control a confluence of environmental conditions, group and place-based identities, and the mechanics and meanings of mobility among seasonal workers. By hiring non-local, seasonal workers and by attempting to control their mobility, large-scale, corporate growers and their spokespeople ultimately sought to maintain control over the development and identity of the valley's rural landscape. (C) 2009 Elsevier Ltd. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-295-443-843-273 tex.type: [object Object]
Keywords: Agriculture; Connecticut; Connecticut Valley; Labor; Mobility; New England; Nicotiana tabacum; Tobacco; United States; agricultural production; dept.egm; environmental conditions; mobility; rural landscape; tobacco; twentieth century

Jaltomata parviflora (Solanaceae) una nueva especie del Norte del Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2010)
Citation Key Alias: pop00185 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

Book Review: A review of “Cultural landscapes” - Yacher, Leon (The Professional Geographer, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-201-209-871-369 tex.type: [object Object]
Keywords: book.review; dept.egm

Photojournal: distant beats: tradition and change in senegal - Yacher, Leon (Focus on Geography, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-871-272-049-905 tex.type: [object Object]
Keywords: Senegal; cultural change; cultural geography; cultural influence; cultural landscape; cultural tradition; dept.egm; music

Diel and tidal pCO2 × O2 fluctuations provide physiological refuge to early life stages of a coastal forage fish - Cross, Emma L.; Murray, Christopher S.; Baumann, Hannes (Scientific Reports, 2019)
Coastal ecosystems experience substantial natural fluctuations in pCO2 and dissolved oxygen (DO) conditions on diel, tidal, seasonal and interannual timescales. Rising carbon dioxide emissions and anthropogenic nutrient input are expected to increase these pCO2 and DO cycles in severity and duration of acidification and hypoxia. How coastal marine organisms respond to natural pCO2 × DO variability and future climate change remains largely unknown. Here, we assess the impact of static and cycling pCO2 × DO conditions of various magnitudes and frequencies on early life survival and growth of an important coastal forage fish, Menidia menidia. Static low DO conditions severely decreased embryo survival, larval survival, time to 50% hatch, size at hatch and post-larval growth rates. Static elevated pCO2 did not affect most response traits, however, a synergistic negative effect did occur on embryo survival under hypoxic conditions (3.0 mg L-1). Cycling pCO2 × DO, however, reduced these negative effects of static conditions on all response traits with the magnitude of fluctuations influencing the extent of this reduction. This indicates that fluctuations in pCO2 and DO may benefit coastal organisms by providing periodic physiological refuge from stressful conditions, which could promote species adaptability to climate change.
15 citations (Crossref) [2023-10-31]
Keywords: dept.egm

The blue economy: Identifying geographic concepts and sensitivities - Garland, Michaela; Axon, Stephen; Graziano, Marcello; Morrissey, John; Heidkamp, C. Patrick (Geography Compass, 2019)
There is currently no generally accepted definition for the “blue economy,” despite the term becoming common parlance over the past decade. The concept and practice have spawned a rich, and diverse, body of scholarly activity. Yet despite this emerging body of literature, there is ambiguity around what the blue economy is, what it encapsulates, and its practices. Thus far, the existing literature has failed to theorise key geographical concepts such as space, place, scale, and power relations, all of which have the potential to lead to uneven development processes and regional differentiation. Previous research has sought to clarify the ontological separation of land and sea or has conceptualised the blue economy as a complex governmental project that opens up new governable spaces and rationalises particular ways of managing marine and coastal regions. More recently, geographers have called for a critical—and practical—engagement with the blue economy. This paper critically examines the existing literature of the geographies of the blue economy through a structured meta-analysis of published work, specifically its conceptualisations and applications to debates in the field. Results offer the potential to ground a bottom-up definition of the blue economy. In so doing, this paper provides a clearly identifiable rubric of the key geographical concepts that are often overlooked by researchers, policymakers, and practitioners when promoting economic development and technological innovation in coastal and marine environments. © 2019 The Author(s) Geography Compass © 2019 John Wiley & Sons Ltd
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-155-049-386-765, pop00266 tex.type: [object Object]
Keywords: coastal zone; conceptual framework; dept.egm; economic development; economics; innovation; marine environment; peer-reviewed; power relations; uneven development

Thicker shells compensate extensive dissolution in brachiopods under future ocean acidification - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Environmental Science & Technology, 2019)
26 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

Development of an ecoregional floristic quality assessment method for the northeastern united states - Faberlangendoen, Don; Cameron, Don; Gilman, Arthur V; Metzler, Kenneth J; Ring, Richard M; Sneddon, Lesley (Northeastern Naturalist, 2019)
Floristic quality assessments (FQA) are widely used to assess ecological condition, based on plant species' coefficients of conservatism, or C values, but these values are typically assigned at the state level, limiting their regional consistency. We developed ecoregional C values (eC) using standard expert-based team review, partly informed by preexisting state C values for the 5 EPA ecoregions that cover New England and part of New York. We evaluated a total of 3686 taxa, with separate eC values for each ecoregion in which they occurred. We compared the performance of the C and eC values using the response of FQA metrics (mean C, cover-weighted mean C) to a disturbance gradient, based on readily available datasets in Maine and Vermont. The eC values typically performed moderately better than state values and provide a region-wide tool for assessment methods. All eC values are available on the Universal FQA website. © 2019 Humboldt Field Research Institute. All rights reserved.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-913-936-427-273 tex.type: [object Object]
Keywords: dept.egm; peer-reviewed

Book Review: Home, nature, and the feminine ideal: Geographies of the interior and of empire, Elaine Stratford, Rowman & Littlefield, Lanham, MD (2019), 323 pages, US150.00 hardcover - Thompson, Carolyn (Journal of Historical Geography, 2019)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-875-764-558-138 tex.type: [object Object]
Keywords: book.review; dept.egm

Robust quantification of fish early life CO2 sensitivities via serial experimentation - Baumann, Hannes; Cross, Emma L.; Murray, Chris S. (Biology Letters, 2018)
16 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

Data and policy scale mismatch in coastal systems : The potential of μUAS as new tools for monitoring coastal resilience - Graves, Scott M. (Towards Coastal Resilience and Sustainability, 2018)
An important challenge in monitoring, planning and evaluating coastal saltmarsh resources in the face of predicted sea level rise (SLR) using numerical
Keywords: 3D modeling; Antennas; Coastal systems; Flight planning; Model results; Numerical models; Remotely sensed data; Scale mismatches; Sea level; Sea level rise; Structure from motion; Unmanned aerial systems; Unmanned aerial vehicles (UAV); Wetlands; dept.egm

Conclusion: Outlook for coastal transitions - Heidkamp, C. Patrick; Morrissey, John; Morrissey, John (Towards Coastal Resilience and Sustainability, 2018)
Globally, rapid demographic change of coastal urban agglomerations, the speed of urbanisation over time, the overall impact of coastal space occupation as well
Keywords: Climate change; Coastal ecosystems; Coastal zones; Demographic changes; Economics; Ecosystem services; Ecosystems; Energy availability; Flood control; Impervious surface; Long term process; Sea level; Topography; Urban agglomerations; Urban development; Urban growth; dept.egm

Harnessing place attachment for local climate mitigation? Hypothesising connections between broadening representations of place and readiness for change - Upham, Paul; Johansen, Katinka; Bögel, Paula Maria; Axon, Stephen; Garard, Jennifer; Carney, Sebastian (Local Environment, 2018)
7 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

The human factor: Classification of European community-based behaviour change initiatives - Axon, Stephen; Morrissey, John; Aiesha, Rosita; Hillman, Joanne; Revez, Alexandra; Lennon, Breffní; Salel, Mathieu; Dunphy, Niall; Boo, Eva (Journal of Cleaner Production, 2018)
Behaviour, practices and culture constitute a powerful human factor in the energy system; in particular the interactions between technologies, practices and norms lock individuals in to certain patterns of (often inefficient) energy use. Consequently, behaviour change has gained traction amongst policy makers as a key area of intervention given the impact energy-related behaviours have on climate change. Given the increasing emphasis within policy perspectives in the European Union, it is surprising that a gap in understanding of the success factors of behaviour change initiatives remains. This paper addresses this gap by identifying and characterising behaviour change initiatives across five European countries (the UK, Ireland, France, Italy, and Spain). The paper provides insights into the success factors and commonly encountered barriers to behaviour change initiatives. Initiatives are classified into 6 broad categories (community-based interventions; information and awareness based interventions; eco-districts; show-case events; energy switching; and smart-technology focused interventions). The results suggest that there are significant knowledge gaps between what is known to work to engage individuals in behavioural change and what is currently being applied in practice. An over-reliance on education and awareness-raising projects is evident, illustrating that such projects do not sufficiently aim for sustained behavioural changes. A dearth of projects incorporating fiscal measures, regulations or legislation to drive behaviour change reflects reluctance on behalf of decision-makers to engage widely with diverse approaches to foster lifestyle change. This paper contributes understandings of the different models and delivery tools employed to change energy-related behaviours; insights into the critical success factors that underpin best practice and the barriers to action; and a `what works in practice' overview of the meaningful approaches to change behaviour. (C) 2018 Elsevier Ltd. All rights reserved.
49 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000428826300052, lens.org/074-077-572-550-519 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Behaviour change; Behaviour changes; Binary alloys; Climate change; Decision making; Energy; Europe; Human engineering; Interventions; Laws and legislation; Potassium alloys; Practices; Sustainability; Sustainable development; Uranium alloys; dept.egm; peer-reviewed

A 120-year record of resilience to environmental change in brachiopods - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Global Change Biology, 2018)
21 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

Social enterprise as a potential niche innovation breakout for low carbon transition - Hillman, Joanne; Axon, Stephen; Morrissey, John (Energy Policy, 2018)
While there is growing consensus that human behaviours need to change to a more sustainable paradigm, community driven approaches, such as social enterprise, have yet to be explored as serious instruments of sustainability transition. Social enterprises sit within the third sector of the economy, typically where market or governmental failures exist in the provision of social welfare, and have increasingly become a key driver of social progress. The autonomous nature of the social-economic model applied by such organisations can represent a viable means to reduce state social welfare dependence, and is a proven model for social change. The capability of social enterprises to create both social and economic value is considered a `win-win'. Yet there are clear potentials for social enterprise models to be more extensively applied to address contemporary ecological challenges of neo-liberal market economies, moving towards `win-win-win' outcomes across social, economic and ecological domains. This paper investigates the value of social enterprises as drivers of low-carbon transition at the community level, with an emphasis on the energy sector. Evidence from seven organisations in the UK is presented and a socio-technical transitions conceptual framework is applied to analyse these social enterprise operations as a form of social innovation.
59 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000431932600044, lens.org/059-051-520-983-647 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Behavioral research; Carbon; Commerce; Conceptual frameworks; Ecology; Energy; Innovation; Low-carbon transitions; Social Enterprise; Social enterprise; Social innovations; Socio-technical regimes; Socio-technical transitions; Sustainability Transitions; Sustainability transition; Sustainable development; United Kingdom; carbon; carbon emission; dept.egm; emission control; environmental economics; innovation; sustainability; welfare provision

Examining historical land management and current urban forest health - Massa, Amanda; Zavar, Elyse; Lavy, Brendan L.; Graves, Scott M. (Northeastern Geographer, 2018)
Urban forests can serve as valuable oases for birds and other wildlife in densely-populated urban and suburban areas with proper management. This study analyzes forest health and habitat availability of a publically-owned urban forest in West Haven, Connecticut. During the first half of the twentieth-century, this urban forest was privately-owned and primarily managed as an orchard and meadow for grazing horses. By the mid-twentieth-century, farming dwindled on the land and vegetation overtook the property. Today, this closed-canopy forest, with access to both freshwater streams and marshlands, provides habitat to a variety of native and invasive plant and animal species. By identifying the forest species and characteristics of the six hectare Cove River Historic Site (CRHS) urban forest, this study serves as the first forest inventory and provides a baseline dataset to help manage an ecologically important urban forest. Additionally, we identified bird habitat opportunities and bird species at the property. This study considers both the historic land management practices of this site in tandem with present-day forest health and animal activity to understand how this fragmented forest contributes to local biodiversity. The results indicate that this property, located within the urban environment of the central Connecticut coastline, offers varied habitats and food sources for many resident and migratory bird species, as well as wildlife including foxes.
Keywords: BIRD habitats; FOREST health; LAND management; MIGRATORY birds; URBAN forestry; bird habitat; conservation; dept.egm; invasive species; land management; peer-reviewed; urban forestry; ⛔ No DOI found

A transitions perspective on coastal sustainability - Morrissey, John; Heidkamp, C. Patrick (Towards coastal resilience and sustainability, 2018)
This chapter presents a review of the multi-scalar complexities of coastal sustainability challenges. It focuses on three discrete vignettes of innovation, which range from a novel and emerging innovation, a maturing innovation and an innovation which has become mainstream and part of the prevailing socio-technical regime. The first vignette focuses on 3D ocean farming off the coast of Connecticut in Long Island Sound, USA, as an example of an emerging niche-level innovation. The second vignette discusses the development of offshore wind energy capacity in Liverpool Bay, UK as an example of a socio-technical innovation that is more mature. The final vignette discusses containerisation as an example of a fully matured socio-technological change. The chapter argues that a spatial perspective on transition is critical to adequately account for uneven development processes and to recognise the heterogeneity of different places in terms of potential for low-carbon transition. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Barium alloys; Coastal sustainability; Development process; Liverpool bays; Low-carbon transitions; Off-shore wind energy; Offshore oil well production; Socio-technical regimes; Sociotechnical; Sustainable development; Technological change; Wind power; dept.egm

Towards a just assessment tool for identifying food deserts using a space-time economic model. - Ritchie, Michelle; Heidkamp, C. Patrick; Frazier, Tim (Northeastern Geographer, 2018)
Keywords: dept.egm; peer-reviewed; ⛔ No DOI found

Coastal sediment management as a response to intensifying storms and sea level rise: A case study - Tait, James; Orlowski, Ryan; Brewer, Jessica; Miller, Matthew D (Towards coastal resilience and sustainability, 2018)
In a period of rising sea levels and intensifying storms, enhancing coastal resilience and finding sustainable ways of living with the coast have become necessary concerns. Investigations of storm wave damage to coastal structures on the Connecticut shoreline during Hurricane Irene and Superstorm Sandy revealed that the width and height of frontal beaches were the most common denominator in mitigating the damages. One of the major problems, particularly for a state like Connecticut that has a highly developed coastline with systematically eroding beaches, is that the cost of beach nourishment projects is not only high but is increasing rapidly. The cost of beach nourishment at Prospect Beach in the town of West Haven is instructive. However, considering the importance of beaches and the costs of replenishment, rethinking Environmental Protection policies in favour of instituting regional and local sediment management practices may be in order. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Beach nourishment; Beach nourishment projects; Beaches; Coastal sediments; Coastal structures; Common denominators; Sea level; Sea level rise; Sediment management; Shore protection; Storm waves; Storms; Sustainable development; dept.egm

The human geographies of coastal sustainability transitions - Axon, Stephen (Towards coastal resilience and sustainability, 2018)
This chapter provides an overview of public engagement, its importance and effective approaches to meaningfully involve the public with coastal sustainability transitions. It presents two case studies, Guernsey, British Channel Islands and Cape Wind, Massachusetts. These illustrate how concepts of identity, marginality and engagement are essential to the development of coastal sustainability transitions. As the case study of Guernsey outlines, coastal sustainability transition-related public engagement should seek to enhance the local distinctiveness of coastal areas and 'fit within the wider narrative of place identity and how individuals feel attached to places that are ascribed with specific meanings'. Furthermore, as the case study of Cape Wind illustrates, coastal sustainability transitions need to connect with local communities in terms of addressing immediate social and economic concerns. Therefore, as a research agenda, the human geographies of coastal sustainability transitions can be of substantial value to the practical application of sustainability. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Case-studies; Coastal sustainability; Economic concerns; Effective approaches; Local community; Massachusetts; Public engagement; Research agenda; Sustainable development; dept.egm

“Keeping the ball rolling”: Addressing the enablers of, and barriers to, sustainable lifestyles - Axon, Stephen (Journal of Environmental Psychology, 2017)
The impetus for addressing climate change is real and present, but its translation into action lacks immediacy and severity, and involves reorientating our lifestyles and economies towards sustainability. Drawing on focus groups conducted in seven UK communities, specific interventions were identified as encouraging change in the short-term, maintaining momentum in the medium-term and sustaining sustainability in the long-term to address various enablers of, and barriers to, sustainable lifestyles. The findings illustrate that there are multiple entry points and influencing periods for sustainable living. Given the importance of the temporal dimension in encouraging and sustaining practices for sustainable lifestyles, the paper advances a “what works” approach to sustainable lifestyles that can be embedded with practical solutions. This approach creates a synergy between what individuals want to do to live sustainably and how they want to do this with interventions that are known to create meaningful lifestyles changes and maintain sustainable living.
52 citations (Crossref) [2023-10-31]
Keywords: Addressing climate change; Barriers; Enablers; Interventions; Social practices; Sustainable lifestyles; dept.egm

Stakeholder engagement in coastal sustainability transitions: an emerging research agenda - Axon, Stephen; Chapman, Anya; Light, Duncan (Regions Magazine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Coastal sustainability ii: frontiers for regional transition towards sustainability transitions in the coastal zone - Morrissey, John E.; Heidkamp, Patrick (Regions Magazine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Land-use change at temporary group-housing sites in post-Katrina Louisiana - Zavar, Elyse; Hagelman, III, Ronald; Lavy, Brendan; Prince, Benjamin (Natural Hazards Review, 2017)
To shelter the large number of displaced households following Hurricane Katrina (2005), FEMA, in conjunction with local governments, established 110 temporary group-housing sites throughout impacted Louisiana. The purpose of this study is to identify how temporary group-housing sites influenced the land use of post-Katrina Louisiana. Using aerial imagery, this study assessed the land use of each temporary group-housing site prior to Hurricane Katrina in 2005 and again in 2010. Of the 110 group-housing sites, 54.5% reverted to the previous land use, 29.1% returned to the previous land use with improvements, and 16.3% of the sites changed land use. Using census data from 2000 and 2010, site characteristics, and property records, this study employed a multinomial logistic regression to identify statistically significant variables in predicting land-use change in post-Katrina Louisiana. The results indicate that, especially in neighborhoods with high demand for land, FEMA temporary group-housing sites tended to be redeveloped into new land uses.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/146-296-911-884-194 tex.article-number: [object Object] tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Aerial imagery; Aerial photography; Group housing; Housing; Hurricane Katrina; Hurricane Katrina 2005; Hurricane katrina; Hurricanes; Land use; Land-use change; Local government; Louisiana; Multinomial logistic regression; Population statistics; Significant variables; Site characteristics; Temporary group housing; United States; aerial photograph; census; dept.egm; hazard assessment; hazard management; housing project; land use change; local government; neighborhood

Geospatial sculpture: Nonverbal communication through the tactilization of geospatial data - Heidkamp, C. Patrick; Slomba, Jeffrey T. (GeoHumanities, 2017)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-225-748-349-137, pop00234
Keywords: 3D visualization; Connecticut; Escultura Geoespacial; GeoSpatial Sculpture; dept.art; dept.egm; geografías no verbales; nonverbal geographies; peer-reviewed; tactilización; tactilization; visualización en 3D; 三维可视化; 地理空间雕塑; 康涅狄格; 触觉化; 非语言的地理

El género Jaltomata Schltdl. (Solanaceae) en la región La Libertad y un nuevo taxón del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00298 tex.type: [object Object]
Keywords: dept.egm

Coastal Sustainability I: Challenges, Methods and Opportunities - Heidkamp, C. Patrick; Morrissey, John E. (Regions Magazine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Assessing the transition potential of 3D ocean farming in Long Island Sound - Kelly, Erin; Heidkamp, Patrick; Miller, Matthew D. (Regions Magazine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

µUAS: New tools for monitoring coastal resilience - Graves, Scott M (Regions, 2017)
Keywords: dept.egm; ⛔ No DOI found